2015
DOI: 10.1167/iovs.15-17294
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis of Molecular Risk Factors in the Ocular Hypertensive Human Retina

Abstract: This study provides information about ocular hypertension-related molecular risk factors for glaucoma development. Molecular alterations detected in the ocular hypertensive human retina as opposed to previously detected alterations in human donor retinas with clinically manifest glaucoma suggest that proteome alterations determine the individual threshold to tolerate the ocular hypertension-induced tissue stress or convert to glaucomatous neurodegeneration when intrinsic adaptive/protective responses are overw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 81 publications
0
28
0
Order By: Relevance
“…Moreover, retinas from DBA/2J mice aged 12 to 14 months exhibited a significant reduction in the steady-state levels of mitochondrial proteins involved in energetic metabolism, organelle dynamics, or antioxidant defenses. Proteomic studies investigating human retina samples from glaucomatous or ocular hypertensive patients established that an array of mitochondrial proteins displayed significant level reductions 47, 48. Consequently, insufficiency in the energy supply could initiate defects in electrical conduction and axonal transport, thereby leading to neuronal cell loss and, ultimately, glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, retinas from DBA/2J mice aged 12 to 14 months exhibited a significant reduction in the steady-state levels of mitochondrial proteins involved in energetic metabolism, organelle dynamics, or antioxidant defenses. Proteomic studies investigating human retina samples from glaucomatous or ocular hypertensive patients established that an array of mitochondrial proteins displayed significant level reductions 47, 48. Consequently, insufficiency in the energy supply could initiate defects in electrical conduction and axonal transport, thereby leading to neuronal cell loss and, ultimately, glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…This may be particularly detrimental for non-dividing cells such as those in the TM and the retina since the accumulated material would not be diluted by distribution to daughter cells. A recent proteomics study showed many proteins linked to the ubiquitination pathway are up-regulated in hypertensive human retinas (Yang et al, 2015b). Interestingly, two up-regulated proteins identified in this hypertensive study, HSPB1 and UBC, were identified to bind to ASB10 (Andresen et al, 2014).…”
Section: Asb10 Expression and Functionmentioning
confidence: 99%
“…The longer the injury lasts or the more dramatically increased the IOP is, the greater the extent of the immediate increase in autophagy is, inducing RGC death in a relatively short period of time [105]. Additionally, various proteins involved in cellular redox homeostasis and the OS response were upregulated in the retinas of ocular hypertensive humans [106]. In a retinal ischemia-reperfusion (I/R) model, the loss of neurons in the RGC layer was more severe in Nrf2 KO mice than in wild-type mice, and the RGC activity of Nrf2 KO mice was reduced, indicating that Nrf2 had an inherent protective effect in RGCs [107].…”
Section: Fuchs' Endothelial Corneal Dystrophy (Fecd)mentioning
confidence: 99%